Edukasi Penggunaan Teknologi yang Bijak di SDN 020 Tarakan - Nurul Hidayat; Alvina Alvina (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Nowadays technology is developing rapidly, one of which is gadget. Gadget is one of the physical forms of technology that always develops from year to year. Besides having uses and facilitating human life. Excessive use of gadgets has many adverse effects on health and development and growth in early childhood. This can happen because of the impact that can trigger excessive consumptive behavior. In addition, it also causes children to become introverted or more closed due to lack of social interaction. This socialization aims to provide education about gadgets in early childhood in order to realize quality education. Although technology was originally created to produce a positive impact, on the other hand technology also has a negative impact. For example, like gadgets. Gadgets can have a negative impact such as online game addiction which is bad for children's physical and psychological health. The dangers posed by the use of gadgets are a serious concern to be addressed immediately in order to minimize the negative impact of gadget use on early childhood, especially on children in elementary school. This socialization was conducted for 1 day at SDN 020 Tarakan and was attended by 28 students of class 4A at SDN 020 Tarakan. With this socialization, it is hoped that children will be able to understand the negative impact of using gadgets and it is proven by children who are able to answer questions.